Mucosal cytokine network in inflammatory bowel disease - Andoh, Akira (The WJG Press and Baishideng, 2008)
Inflammatory bowel disease (IBD), ulcerative colitis (UC) and Crohn’s disease (CD) are characterized by ongoing mucosal inflammation in which dysfunction of the host immunologic response against dietary factors and commensal bacteria is involved. The chronic inflammatory process leads to disruption of the epithelial barrier, and the formation of epithelial ulceration. This permits easy access for the luminal microbiota and dietary antigens to cells resident in the lamina propria, and stimulates further pathological immune cell responses. Cytokines are essential mediators of the interactions between activated immune cells and non-immune cells, including epithelial and mesenchymal cells. The clinical efficacy of targeting TNF-α clearly indicates that cytokines are the therapeutic targets in IBD patients. In this manuscript, we focus on the biological activities of recently-reported cytokines [Interleukin (IL)-17 cytokine family, IL-31 and IL-32], which might play a role through interaction with TNF-α in the pathophysiology of IBD.